2x+7x=10x-4

Simple and best practice solution for 2x+7x=10x-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+7x=10x-4 equation:


Simplifying
2x + 7x = 10x + -4

Combine like terms: 2x + 7x = 9x
9x = 10x + -4

Reorder the terms:
9x = -4 + 10x

Solving
9x = -4 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
9x + -10x = -4 + 10x + -10x

Combine like terms: 9x + -10x = -1x
-1x = -4 + 10x + -10x

Combine like terms: 10x + -10x = 0
-1x = -4 + 0
-1x = -4

Divide each side by '-1'.
x = 4

Simplifying
x = 4

See similar equations:

| Y+2x+10=180 | | 2(n+5)=n+19 | | 5p+2=4-1 | | 7-7q=-15+-9q | | (4y^3-y-1)-(2y^2-3y+7)=0 | | 8y-2=-3(y-3) | | x*x+6x+9=-3x+1 | | 2+12x=123x | | 6-9x=36-13x | | 9st(7s-6t^2)= | | x+6x+9=-3x+1 | | 7(7+6)=x(x+4) | | 180=y+(5x+20) | | -12-15x=33 | | 6(v-9)=-2v-14 | | 9(3n-3)=(4n+8)+2 | | 0.3x+3=-2.3x+0.4 | | 7(x-1)+3(3-x)=5(1-x)-3(2x+1) | | 2(90-x)-6=124 | | 961=400+2x | | 15+5(x-10)=3(x-1) | | 16x+16=16x-16 | | 13t-52+8t=21t+28-10 | | 5(z+1)=z+8 | | 5+-6= | | 180=y+5x+20 | | 12x+4=1(x+12) | | -8x-12=36 | | -11+-9= | | 5x+2(x+7)=6x+14 | | -8z-18=-10 | | 11/27=4/9-2x/3 |

Equations solver categories